Manual of Nephrology - Shetty, S. D. Shrimati Dharmapal; Kher, V. Vijay (Jaypee Brothers Medical Publishers, 2016)
Nephrology is a specialty of medicine and pediatrics that concerns itself with the study of normal kidney function, kidney problems, the treatment of kidney problems and renal replacement therapy. India is the world's capital for type II diabetes and the chronic kidney disease burden is thus going to be ever increasing. This book "manual of nephrology" consists of total 15 chapters. This book will act as a quick-reference guide to deal with day-to-day renal problems in the patients. It is replete with informative tables, flow charts for quick glance, self-explanatory figures, recent guidelines and concise text for maximum understanding of the subject in a simple yet effective way. This book will benefit medical interns, postgraduate students, practicing physicians, nephrology fellows and clinicians.